Improving the care of patients with COVID-19 with a medical student-run telemedicine clinic. Issue 1 (18th March 2022) - Wees, Isabel; Murtuza, Mohammad Imran; Mathisen, Danielle; Zhang, Helena; Roy, Mathews; Phelps, Eleanor; Reed, Gary
Abstract : Introduction: In March 2020, the Dallas Fort Worth Metroplex experienced a surge in acute COVID-19 infections. At that time, no consistent protocols existed for follow-up of discharged patients with COVID-19 from the William P Clements Jr University Hospital at the University of Texas Southwestern Medical Center. Simultaneously, medical students were suspended from in-person clinical activities to limit viral spread. In response to these events, a telemedicine elective was created to provide timely and high-quality telehealth follow-up for recently discharged patients with COVID-19. Methods: The pilot team, consisting of several second-year through fourth-year medical students, developed a call script that included warning signs and symptoms, Centers for Disease Control and Prevention (CDC) guidelines for isolation and primary care physician referral information. Patients with COVID-19 discharged from the emergency department (ED) and inpatient services were identified and assigned to student callers. All patients were discussed with an attending physician, who was available if an acute issue arose. The elective also included education on the SBAR (situation, background, assessment, and recommendation) handover technique, telehealth education, updated COVID-19 literature and CDC guidelines. Results: Improvement was noted in students' ability to identify patients who required escalation of care, as seen by over 60% of patients who were advised to return to ED required hospital admission. Statistically significant improvement was observed in the students' degree of feeling informed about the current state of COVID-19 and their degree of comfort with interviewing patients over the phone. Discussion: This elective provided quality virtual healthcare to patients with COVID-19 while allowing medical students to progress in their medical education and participate in patient care.